A comparison of perceptual anticipation in combat sports between experts and non-experts: A systematic review and meta-analysis - Zhang, Zhen; Piras, Alessandro; Chen, Chao; Kong, Bin; Wang, Dexin (Frontiers in Psychology, 2022)
In order to systematically evaluate perceptual anticipation between experts and non-experts for different kinds of combat sports, we needed to perform a comprehensive assessment. In this systematic review and meta-analysis, we searched four English-language and three Chinese-language databases that used expert/non-expert research paradigms, to explore perceptual anticipation in combat sports. We employed a random effects model for pooled analyses using the inverse variance method. We included 27 eligible studies involving 233 datasets in this meta-analysis. We observed large effect sizes for the differences between experts and non-experts in both response accuracy (1.51; 95% CI: 1.15 to 1.87, p<0.05) and reaction time (-0.91; 95% CI: -1.08 to -0.73, p<0.05). We also observed substantial differences between experts and non-experts in the mean duration of visual fixations per trial (1.51; 95% CI: -2.40 to -0.63, p<0.05), but not in the visual fixation duration (0.16; -061 to 0.92, p=0.69). Taken together, high-level combat athletes have more advantages in perceptual anticipation than lower-level athletes, showing faster and more accurate responses when facing the opponent’s attacks, as well as focusing on fewer points of visual fixations than novice athletes. Different types of combat sports and stimulus presentations affect perceptual anticipation abilities to varying extents in relation to outcome measures, with more pronounced expertise in a stimulus that is closer to real-world situations.